Project management : all-in-one for dummies - Graham, Nick; Layton, Mark C. ;Morrow, David ;Ostermiller, Steven J. ;Portny, Stanley E. ;Rose, Doug ;Dionisio, Cynthia Snyder (Hoboken, New Jersey : John Wiley & Son, Inc., 2020)
In today's time-crunched, cost-conscious global business environment, tight project deadlines and stringent expectations are the norm. So how can you juggle all the skills and responsibilities it takes to shine as a project management maven? Updated in a brand-new edition, Project Management For Dummies offers everything you need to successfully manage projects from start to finish--without ever dropping the ball. Written by a well-known project management expert, this hands-on guide takes the perplexity out of being a successful PM, laying out all the steps to take your organizational, planning, and execution skills to new heights. Whether it's managing distressed projects, embracing the use of social media to drive efficiency and improve socialization, or resolving conflicts that occur during a project, the soup-to-nuts guidance inside will help you wear your project management hat more prominently--and proudly.
Book 1. In the beginning: project management basics. Achieving results with project management -- Involving the right people -- Developing your game plan -- Book 2. Steering the ship: planning and managing a project. You want this project done when? -- Starting your project team off on the right foot -- Monitoring progress and maintaining control -- Bringing your project to closure Book 3. Helping out: using tools on a project. Considering checklists and templates -- The key documents for managing a project ; Working with Microsoft Project 2019 -- Surveying cool shortcuts in Project 2019 -- Book 4. A new method: agile project management. -- Applying the agile manifesto and principles -- Defining the product vision and product roadmap -- Planning releases and sprints -- Working throughout the day -- Showcasing work, inspecting, and adapting -- Book 5. A popular agile approach: running a scrum project. The first steps of scrum -- Planning your project -- The talent and the timing -- Release and sprint planning -- Getting the most out of sprints -- Inspect and adapt: how to correct your course -- Book 6. The next level: enterprise agility. Taking it all in: the big picture -- Sizing up your organization -- Driving organizational change -- Putting it all together: taking steps toward an agile enterprise -- Book 7. Making it official: PMP certification. Introducing the PMP exam -- It's all about the process -- Reviewing the PMI code of ethics and professional conduct.
Includes bibliographical references and index.
Keywords: LEADERSHIP